Leaf water potential effects on coffee (Coffea arabica, L.) plant flowering induction and yield - Rezende, Fátima Conceição; Faria, Manoel Alves de; Miranda, Weser Lismar (Coffee Science - ISSN 1984-3909, 1970)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> An experiment was carried out in Lavras/MG aiming to correlate the leaf water potential with flowering and yields from coffee (Coffea arabica, L.) Cv. Topazio, MG-1190 that was submitted to a severe pruning 65 months after planting. The orchard was implanted in a 1.8 X 0.7m spacing and was drip irrigated. A complete randomized experimental design with six treatments and four replications was implemented. Treatments corresponded to six different irrigation periods: E0 (control without irrigation), E1 (without irrigation from June to July), E2 (without irrigation in July), E3 (irrigation only from April to May), E4 (irrigation only from April to June), E5 (irrigation all year around). Irrigations were held every Tuesday and Friday. The applied irrigation depth was equivalent to 100% of the balance between the evaporation depth from a class “A” pan and the precipitation depth measured during the time interval between two successive irrigations (ECA-P). Fertilization with just Nitrogen and Potassium was split in 4 applications, under canopy throughout the period from October to March. Pre-dawn leaf water potential was evaluated from April to September, number of flowers was measured, from September to December, at four branches in all replications of each treatment, and at harvest time the yields were evaluated. It was observed that water deficits induced by irrigation suppression were not able to promote flowering concentration but the irrigation suppression during the months of June and July promoted economy of water and energy as well as an increase in the accumulated production of the three harvests.